Levitt, P.: God needs no Passport. Immigrants and the changing American Religious Landscape - Eguren, Joaquín (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The New Press, New York, London, 2007, 270 pp